2006
DOI: 10.1080/09595230600644699
|View full text |Cite
|
Sign up to set email alerts
|

Providing opioid substitution treatment to Indigenous heroin users within a community health service setting in Adelaide

Abstract: In the late 1990s there was major concern regarding heroin use among the Nunga community in Adelaide. [Nunga is a generic term used for Aboriginal people from South Australia, similar to Koori's from Victoria and Nyungars from south-western Australia.] Heroin use was so common that community members reported that most families were affected by it in some way. There were few Nunga specific services provided, and those mainstream services available were not seen as culturally appropriate or for other reasons wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 3 publications
0
45
0
Order By: Relevance
“…Since these earlier studies, culturally-centered MAT services have been successfully implemented with Indigenous people in Australia and Canada (1921). In Australia, success was attributed to the culturally-specific design, integrated care, and a focus on family and community wellness (21).…”
Section: Pharmacological Treatment Of Opioid Use Disorder With Ai/ansmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these earlier studies, culturally-centered MAT services have been successfully implemented with Indigenous people in Australia and Canada (1921). In Australia, success was attributed to the culturally-specific design, integrated care, and a focus on family and community wellness (21).…”
Section: Pharmacological Treatment Of Opioid Use Disorder With Ai/ansmentioning
confidence: 99%
“…In Australia, success was attributed to the culturally-specific design, integrated care, and a focus on family and community wellness (21). In Canada, patients reported positive treatment outcomes, improvements in housing, employment, and family support, and general satisfaction and acceptance of MAT (20).…”
Section: Pharmacological Treatment Of Opioid Use Disorder With Ai/ansmentioning
confidence: 99%
“…The findings are consistent with the successful community health service program for Aboriginal heroin users in Adelaide. 19 It is this supportive framework that enables people to achieve the stability required to remain in maintenance treatment.…”
Section: Heroin Use (Days Per Month)mentioning
confidence: 99%
“…Winnunga has offered opioid replacement pharmacotherapy since 1999 to patients who are opioid-dependent. As in other urban Indigenous communities, 18,19 there was ambivalence to the introduction of harm minimisation strategies with many people supporting abstinence models to address drug addiction. Community support for opioid replacement pharmacotherapy was achieved through discussions between the Winnunga Board, other influential community leaders and the Winnunga staff involved.…”
mentioning
confidence: 99%
“…20 Although this applied to harm reduction strategies, it was suggested that the implementation of methadone maintenance treatment programs within Aboriginal communities can be accompanied by apprehension and distrust. 21 Thus, although individual-level benefits of methadone programs have been established, knowledge on the perceptions and opinions of Aboriginal communities on these programs remains elusive.…”
mentioning
confidence: 99%